Liraglutide improves adipose tissue remodeling and mitochondrial dynamics in a visceral obesity model induced by a high-fat diet - Touceda, Vanessa Michelle (2024)
Central obesity is characterized by visceral adipose tissue (VAT) expansion, considered one of the main risk factors for metabolic complications. In recent years, new drugs have been studied for obesity treatment. Liraglutide (LGT), a GLP-1 agonist, decreases body weight, however, several mechanisms of action on VAT are still unknown. Aim: to study the effect of LGT on factors associated with VAT remodeling and mitochondrial dynamics in mice fed a high-fat diet (HFD). Methods: C57BL/6 mice were divided into Control (C) and HFD. After 15 weeks of feeding, each group was subdivided according to LGT administration for 5 weeks: C, C + LGT, HFD, and HFD + LGT. In epididymal AT (EAT) we evaluated histological and mitochondrial characteristics, vascularity, gelatinase activity (MMPs), and galectin-3 expression. Results: HFD presented larger adipocytes (p < 0.05), and lower vascular density and MMP-9 activity (p < 0.01) than C, while a major number of smaller adipocytes (p < 0.05) and an increase in vascularity (p < 0.001) and MMP-9 activity (p < 0.01) was observed in HFD + LGT. Collagen content was higher (p < 0.05) in EAT from HFD and decreased in HFD + LGT. In C, C + LGT, and HFD + LGT, mitochondria were predominantly tubular-shaped while in HFD mitochondria were mostly spherical (p < 0.001). Conclusion: LGT positively influences VAT behavior by modulating gelatinase activity, enhancing vascularization, and improving adipocyte histological characteristics. Additionally, LGT improves mitochondrial dynamics, a process that would favor VAT functionality.